Pengaruh Profitabilitas Dan GCG Terhadap Nilai Perusahaan LQ45 Di BEI 2023-2024 - Ni Made Mila Lestari Mila Lestari; I Putu Deddy Samtika Putra Tresiana; Ni Made Wisni Arie Pramuki Tresiana (Hita Akuntansi dan Keuangan, 2026)
This study aims to empirically examine the effect of profitability and Good Corporate Governance (GCG) mechanisms on firm value in LQ45 companies listed on the Indonesia Stock Exchange for the period 2023-2024. The independent variables include profitability (ROA), independent commissioners, managerial ownership, institutional ownership, board of directors, and audit committee, while the dependent variable is firm value (PBV). Using purposive sampling, 40 observation data from 20 companies were obtained. Multiple linear regression analysis was employed. The results show that profitability and independent commissioners have a positive and significant effect on firm value. In contrast, managerial ownership, institutional ownership, board of directors, and audit committee do not have a significant effect on firm value. The Adjusted R Square value of 30.9% indicates the explanatory power of the model